2020
DOI: 10.3390/microorganisms8091366
|View full text |Cite
|
Sign up to set email alerts
|

Integrated qPCR and Staining Methods for Detection and Quantification of Enterocytozoon hepatopenaei in Shrimp Litopenaeus vannamei

Abstract: Enterocytozoon hepatopenaei (EHP) is an obligate, intracellular, spore-forming parasite, which mainly infects the gastrointestinal tract of shrimp. It significantly hinders the growth of shrimp, which causes substantial economic losses in farming. In this study, we established and optimized a SYBR Green I fluorescent quantitative PCR (qPCR) assay based on the polar tube protein 2 (PTP2) gene for the quantitative analysis of EHP-infected shrimp. The result showed that the optimum annealing temperature was 60 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Notably, qPCR is often used in the detection of microsporidia and is considered to be more sensitive than conventional PCR (Naung et al, 2020). Wang et al (2020) used qPCR to detect the polar tube protein 2 gene when quantitatively analyzing EHP in infected shrimp and reported that sensitivity was increased by at least two orders of magnitude compared with that of conventional PCR. Phelps and Goodwin (2007) used the same technology to detect Notemigonus crysoleucas and reported that the minimum gene copy number that could be detected in each reaction was as low as 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, qPCR is often used in the detection of microsporidia and is considered to be more sensitive than conventional PCR (Naung et al, 2020). Wang et al (2020) used qPCR to detect the polar tube protein 2 gene when quantitatively analyzing EHP in infected shrimp and reported that sensitivity was increased by at least two orders of magnitude compared with that of conventional PCR. Phelps and Goodwin (2007) used the same technology to detect Notemigonus crysoleucas and reported that the minimum gene copy number that could be detected in each reaction was as low as 10.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have attempted to use qPCR to detect different microsporidia genes, such as those encoding the SSU rRNA, the polar tube protein, tubulin, and the spore wall protein (Jaroenlak et al, 2016;Han et al, 2018;Piamsomboon et al, 2019;Wang et al, 2020). Of these, the SSU rRNA gene carries the most commonly used detection target sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of SDC3 mRNA expression was performed using the primers as follows: 5′-TGG CGC AGT GAG AAC TTC G-3′ (forward) and 5′-CCC CGA GTA GAG GTC ATC CAG-3′ (reverse). Specific PCRs (20 μL) were set up as described previously [17]. The quantitative measures were obtained using the 2 ΔΔCT method.…”
Section: Real-time Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…From 1 g of the sample homogenate prepared by a handheld third-gen TGrinder, the DNA was extracted with a TIANamp Genomic DNA Kit (Tiangen Biotech Co. Ltd., Beijing, China) and quantified with a NanoDrop Lite Spectrophotometer (Thermo Fisher Scientific Inc., Wilmington, DE). The presence of the respective pathogen in the extracted DNA was confirmed by qPCR, as previously reported. DNA of clinical shrimp samples were extracted using the same procedure as mentioned above.…”
Section: Methodsmentioning
confidence: 99%